Investigation of Lyme (Borrelia Burgdorferi) Seropositivity Among The Women With Rheumatism Like Findings in Rural Area of Elaziğ - Erensoy, Ahmet (Fırat University, 2002)
Aim: A total of 140 blood samples were analysed with the purpose of searching lyme (Borrelia burgdorferi) seroprevalance among the women with rheumatic symptoms in Elazığ region. Material and methods: The samples were stored at -20°C in the deep-freeze untill they were analysed. The sera were evaluated EIA test [Immunowell Borrelia burgdorferi (lyme) test]. Results: Seropositivity was determined in 9 (6.43 %) patients. In the 8 of the 9 seropositive patients Rapid Plasma Reagin (RPR) and Romatoid Factor (RF) tests were negative. RPR and RF tests could not be analysed in one patient who did not want to give blood, again. Conclusion: In the lights of the results obtained from the 9 seropositive patients, lyme could be an important public problem in Elazığ in the future. We think that more detailed seroepidemiological studies should be done.

Amaç: Lyme etkeni Borrelia burgdorferi'nin seroprevalansının araştırılması amacıyla Elazığ yöresinde romatizmal yakınmaları olan kadınlardan alınan 140 kan örneği incelendi. Gereç ve yöntem: Kan örnekleri kullanılıncaya kadar -20ºC'de deep-freez'de saklandı. Serumlar, EIA [Immunowell Borrelia burgdorferi (lyme) testi] yöntemi ile B. burgdorferi'ye karşı oluşmuş total antikorlar araştırıldı Bulgular: Toplam dokuz hastada seropozitiflik (% 6.43) saptandı. Seropozitif dokuz olgudan sekiz'inde Rapid Plasma Reagin (RPR) ve Romatoid faktör (RF) testleri negatif bulundu. Bir hasta yeniden kan vermek istemediğinden RPR ve RF testleri çalışılamadı. Sonuç: Seropozitif 9 olgunun incelenmesi sonucu Lyme'ın Elazığ yöresinde gelecekte önemli bir halk sağlığı sorunu olarak karşımıza çıkabileceği kanaatine varıldı. Bu konuda daha geniş çaplı sero-epidemiyolojik çalışmaların yapılması gereğine inanıyoruz.
Elazığ İli Kırsalında Romatizma Benzeri Yakınmaları Olan Kadınlarda Lyme (Borrelıa Burgdorferı) Seropozitifliğinin Araştırılması